2021
DOI: 10.3390/su132112301
|View full text |Cite
|
Sign up to set email alerts
|

Success Factors of SMEs: Empirical Study Guided by Dynamic Capabilities and Resources-Based View

Abstract: This study aims to identify and analyse the success factors of small and medium-sized enterprises (SMEs) following the lines of dynamic capabilities and resources-based views. To achieve this objective, the multiple case study method was followed, where 10 SMEs/cases in Portugal were selected. From a content analysis of the interviews conducted to the owner-managers of these SMEs, the most important success factors identified were: (1) strategic planning, (2) manager/management capacity, (3) entrepreneurship a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 70 publications
0
25
0
4
Order By: Relevance
“…The relevance of these companies for the economic development of countries was also pointed out by Pedauga, Saez, & Delgado-marquez, when they argued that their importance for the business fabric is a recurrent topic in academia, due to the fact that they have constituted a component of the strategic development of many countries [5]. SMEs are basic contributors to the global economy and the knowledge advantage is critical for these firms, while innovation and new product development [6,7], in some sectors, are efficient ways to gain competitive advantage in the market. In addition, the factors that affect the business size of SMEs, such as the characteristics of the entrepreneur, management strategies and the influence of the external environment, constitute elements for the success or failure of a business [8].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The relevance of these companies for the economic development of countries was also pointed out by Pedauga, Saez, & Delgado-marquez, when they argued that their importance for the business fabric is a recurrent topic in academia, due to the fact that they have constituted a component of the strategic development of many countries [5]. SMEs are basic contributors to the global economy and the knowledge advantage is critical for these firms, while innovation and new product development [6,7], in some sectors, are efficient ways to gain competitive advantage in the market. In addition, the factors that affect the business size of SMEs, such as the characteristics of the entrepreneur, management strategies and the influence of the external environment, constitute elements for the success or failure of a business [8].…”
Section: Introductionmentioning
confidence: 87%
“…Moreover, [17] categorized the CSFs for SMEs into three factors: Entrepreneurial factors (owner age, gender, education level, experience and managerial skills), enterprise factors (business age and size, business networks, financial resources, customer relationship management; human capital, marketing and strategic planning) and business environment factors (political, economic, socio-cultural, technological, legal, and ecological environments). [6] investigated factors that affect small business success and concluded that SMEs are oriented towards success, although some evolution is still needed in the way they are managed, where the transition from a "domestic/entrepreneurial" management to a "professional" management and a greater focus on the rarity of their resources and on the dynamic capabilities of their human capital stand out. Conclusions, implications and a future research agenda are also outlined.…”
Section: Figure 1 the Four Layers Of Factors That Determine Smes Upgr...mentioning
confidence: 99%
“…The willingness to work with competitors indicates that employees are ready to improve their knowledge and forge a solid experience. In this vein, managers should promote learning and invest in human resources, allowing employees to improve their skills and expertise to reach the firms' goals (Rodrigues et al, 2021).…”
Section: Conclusion Future Research and Limitationsmentioning
confidence: 99%
“…In general, there are 'soft' and 'hard' factors that influence SMEs' success. Therefore, one can consider customer satisfaction and their acceptance, management capability, entrepreneurial innovativeness, adequate access to financing and information systems, partnerships and governance (Rodrigues, Franco, Silva & Oliveira, 2021). All these characteristics promote a favorable organizational culture.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Speaking of leadership, due to the daily involvement in organizational operations, the behavior of managers/leaders has an impact on organizational members ( (Rodrigues, Franco, Silva & Oliveira, 2021). In other words, it is associated with the ability of one or more individuals at the organizational top, which is linked to the owner's historic role within the organization.…”
Section: Literature Reviewmentioning
confidence: 99%